2018
DOI: 10.3926/jotse.403
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of learning through field study

Abstract: Learning is more concerned in engineering education as students need to do deep learning to understand the engineering principles for practice. Engineering is a practicing profession. Therefore, providing learning environment is required for the subjects of engineering disciplines to enable students to learn in depth. By knowing this phenomenon, field study was conducted as a group study for the civil engineering subject of building construction allowing students to learn and gain knowledge by observing constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…It has been shown that applications let students learn mathematical concepts through practical examples increase students' motivation to study mathematics, as it was confirmed in previous studies like [29]. Moreover, students discover multiple real applications of linear algebra in engineering and other areas, what achieve to motivate them to the study of this subject, as it was developed in previous studies [14,33,34]. From the answers to the questions set to the students in the interviews made after the sessions "Applications of Linear Algebra in Engineering", it can be interpreted that most of the examples have impressed students because they did not know that linear algebra could have applications in so many different disciplines.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…It has been shown that applications let students learn mathematical concepts through practical examples increase students' motivation to study mathematics, as it was confirmed in previous studies like [29]. Moreover, students discover multiple real applications of linear algebra in engineering and other areas, what achieve to motivate them to the study of this subject, as it was developed in previous studies [14,33,34]. From the answers to the questions set to the students in the interviews made after the sessions "Applications of Linear Algebra in Engineering", it can be interpreted that most of the examples have impressed students because they did not know that linear algebra could have applications in so many different disciplines.…”
Section: Discussionmentioning
confidence: 62%
“…Regarding the students' intervention, the main issue has been the relevance of problemsolving in the teaching of mathematics, as it is known that mathematical problem-posing provide better student's critical thinking skills effect than conventional learning [30,36]. Moreover, applications used in basic sciences subjects encourage student engagement and motivation in STEM degrees [14,[33][34][35]. Considering the results shown in Figure 10, it can be seen that 90% of students agreed that applications of mathematical concepts managed to increase their motivation to study linear algebra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies are an important part of research because they help to make the connection between the theoretical knowledge with actual behaviours of water use in the crisis and allowing researchers to better comprehend the real-world circumstances (Kandamby 2018 ; Kundu 2019 ). Due to the current COVID-19 epidemic and lockdown, a predesigned and organised questionnaire was implemented through an internet platform to acquire the information regarding the availability, facilities, and condition of groundwater in the Bankura I and Bankura II blocks.…”
Section: Methodsmentioning
confidence: 99%
“…This is a systematic literature review from a multi-disciplinary style to provide research precision and reliability, where PC is the key unit of scrutiny (Kandamby, 2018). A systematic literature review is a style of literature review that embraces systematic techniques to gather secondary data, objectively evaluate research work and integrate studies.…”
Section: Methodsmentioning
confidence: 99%